1993
DOI: 10.1115/1.2919188
|View full text |Cite
|
Sign up to set email alerts
|

The Stewart Platform of General Geometry Has 40 Configurations

Abstract: The Stewart platform is a six-degree-of-freedom, in-parallel linkage. It is used in automotive and flight simulators, positioning tables for assembly and robotic applications, and various other applications requiring linkages with high structural stiffness. It consists of a base link, a coupler link, and six adjustable-length legs supporting the coupler link. Each leg consists of a prismatic joint with ball-joint connections to the base and coupler, respectively. The forward kinematics problem for the Stewart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
126
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(129 citation statements)
references
References 0 publications
0
126
0
3
Order By: Relevance
“…Determining the pose of the manipulator platform from the linear actuators' lengths (also known as direct kinematics problem) generally leads to a system of algebraic equations that has at most 40 different solutions [1][2][3][4][5][6][7][8]. This number of solutions can be further reduced by introducing additional constraints, for example, combinatorial or planarity constraints [9].…”
Section: Introductionmentioning
confidence: 99%
“…Determining the pose of the manipulator platform from the linear actuators' lengths (also known as direct kinematics problem) generally leads to a system of algebraic equations that has at most 40 different solutions [1][2][3][4][5][6][7][8]. This number of solutions can be further reduced by introducing additional constraints, for example, combinatorial or planarity constraints [9].…”
Section: Introductionmentioning
confidence: 99%
“…For the general case, it was proved that the maximum number of assembly modes was 40 [61,82,86] . In fact, a 40th degree polynomial allowing to calculate (numerically) all possible assembly modes was found by Husty in 1994 [47].…”
Section: Kinematics and Singularities Of Stewart-gough Platformsmentioning
confidence: 99%
“…This method has been responsible for the first solutions of many long-standing problems in Kinematics. For example, using them, Tsai and Morgan first showed that the inverse kinematics of the general 6R manipulator has sixteen solutions [22], Raghavan showed that the direct kinematics of the general Stewart-Gough platform can have forty solutions [23], and Wampler et al solved nine-point path synthesis problems for four-bar linkages [24].…”
Section: Introductionmentioning
confidence: 99%